Tinjauan Hukum Islam Terhadap Tata Cara Pencalonan Presiden di Indonesia: Studi Prinsip Kebebasan Memilih (Al-Ikhtiyar) - Nurfadillah Wilmayanti; Hilda Hinaya; Kurniati Kurniati (Indo Publishing, 2026)
This study examines the presidential nomination mechanism in Indonesia from the perspective of Islamic law, particularly the principle of al-ikhtiyar (freedom of choice). The study aims to analyze the conformity between the nomination procedure regulated under Article 6A of the 1945 Constitution and Law No. 7 of 2017 on General Elections with the Islamic principle that the determination of a leader must be based on the free will of the people, without coercion or manipulation. This study uses a normative legal research method with a statute approach and a conceptual approach, with primary legal materials consisting of legislation, the Qur'an, and Hadith. The results show that Indonesia's presidential election system generally reflects direct popular participation in line with the principle of al-ikhtiyar, but the presidential threshold provision restricts the freedom of political parties to nominate candidates, thereby giving rise to a partial inconsistency with the principle of freedom of choice in Islamic political thought.